Boron adsorption and interaction with phosphate in a volcanic soil from the humid tropic - Fallas Corrales, Róger Armando (2025)
Background: Boron (B) deficiency is a major constraint for crop production in volcanic soils from humid tropical regions. Itsavailability can be influenced by adsorption to short-range order (SRO) minerals and soil organic matter (SOM) and by interactionswith other nutrients.Aims: To analyze the adsorption behavior and surface speciation of B in a volcanic soil from the humid tropics, including itsinteraction with phosphate (PO4 ), and to test the applicability of a mechanistic multi-surface geochemical model for describingthese interactions.Methods: Boron adsorption isotherms were determined on a volcanic soil using two electrolyte solutions (NaNO 3 or CaCl 2 )and two conditions of added PO4 (0 and 1.6 mM). The results were interpreted using an advanced multi-surface ion adsorptionmodel that combines the charge distribution multisite ion complexation (CD-MUSIC) model for describing ion adsorption to SROminerals and the nonideal competitive adsorption (NICA)–Donnan model for adsorption to SOM.Results: The model simulations, conducted in a fully predictive scheme, showed an excellent agreement with the experimental Badsorption data in both NaNO 3 and CaCl 2 solutions, even at micromolar B concentrations. Under natural soil pH conditions, SROminerals were the dominant surfaces controlling B adsorption, whereas SOM played a minor role. The addition of PO 4 had a limitedeffect on B adsorption at low B concentrations; however, a moderate competitive effect was observed at higher B concentrations.Conclusions: This study provides mechanistic insights into B adsorption and speciation in volcanic soils, emphasizing theimportance of SRO minerals as binding surfaces and the limited role of phosphate competition. These findings can contributeto optimize B management in volcanic soils systems from the humid tropics.